Synthesis of Imidazole-Derived Ionic Liquids from Monoterpenes by Means of the Sonogashira Reaction - Speziali, Marcelo G.; Monteiro, Adriano L. (Synthesis, 2012)
This work reports the functionalization of monoterpenoids with 2-iodo-1-methyl-1H-imidazole using Sonogashira cross-coupling reactions. Natural monoterpenes were also modified to obtain the corresponding alkynes which were used in the cross-coupling step. After a sequence of cross-coupling–hydrogenation–N-alkylation–ion metathesis, novel ionic liquids were obtained in reasonable yields. The obtained products can be used as scaffolds for the further synthesis of new ionic liquids derived from terpenoids and for new, potentially bioactive materials, e.g. polycyclic monocationic scaffolds. All obtained products show the characteristics of a room temperature ionic liquid (RTIL).
Keywords: terpenoids; cross-coupling; palladium; ionic liquids; catalysis